Selection parameters for yield and quality traits in Bhut Jolokia (Capsicum chinense Jacq.) under poly-house condition from North East India - Mena, Ephilo; Warade, SD; Dubey, RK; Ansari, Mohd Talha; Ramjan, Md. (Vegetable Science, 2018)
Sixteen genotypes of Bhut Jolokia were evaluated in polyhouse with three replications at vegetable research farm, CHF, CAU, Pasighat, Arunachal Pradesh. Correlation and path analysis were carried out to study the character association and contribution, respectively. Correlation There was a great deal of significant variation for all the characters among the genotypes. In the present investigation, Correlation studies revealed that characters like weight of ripe fruit (0.966, 0.874), fruit length (0.622, 0.503), weight of dry fruit (0.905, 0.805), dry fruit yield per plant (0.903, 0.875) and capsaicin content (0.458, 0.393) was observed significant positive correlation with fruit yield per plant both at genotypic and phenotypic level. However, at genotypic level, weight of ripe fruit had maximum positive direct effect on fruit yield per plant (1.025) followed by dry fruit yield per plant (0.865), fruit length (0.236), ascorbic acid content (0.203). The findings of present study confirmed that, weight of ripe fruit, fruit length, weight of dry fruit, dry fruit yield per plant and capsaicin content were the important characters for selection and chilli breeding programme.